2016
DOI: 10.3109/07420528.2016.1167712
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, social jetlag and sleep debt are associated with dietary intake among Brazilian undergraduate students

Abstract: Undergraduate students experience a form of circadian misalignment - known as "social jetlag" - that represents the discrepancy in timing between their circadian and social clocks. Whilst social jetlag is not dependent upon chronotype, the two phenomena tend to be related; evening types show a tendency to have a greater social jetlag, for example. Moreover, evening types have been found to be more likely to have inadequate eating habits than do morning types. The objective of this study was to examine the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 36 publications
7
98
1
6
Order By: Relevance
“…24 suggest that an activation of the HPA axis resulting from social jetlag may predispose to visceral obesity and other chronic diseases. Factors related to food intake – such as changes in meal distribution across the day 29 and/or the type of food consumed 30 – and physical activity pattern 14, 24 could also explain weight change due to circadian disturbances 25 .…”
Section: Discussionmentioning
confidence: 99%
“…24 suggest that an activation of the HPA axis resulting from social jetlag may predispose to visceral obesity and other chronic diseases. Factors related to food intake – such as changes in meal distribution across the day 29 and/or the type of food consumed 30 – and physical activity pattern 14, 24 could also explain weight change due to circadian disturbances 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased caffeinated drinks in the late chronotype group may provide a potential hypothesis for this issue. Some studies conducted in Brazil, England, and the US have already described that late chronotype is associated with the risk of additional caffeinated drinks intake [16,17,18], promoting beverage addiction and leading to weight gain. In recent years, caffeinated drinks have become more popular, especially in young groups, such as college students.…”
Section: Introductionmentioning
confidence: 99%
“…Although sleep disturbances are known to affect health and behavior, 6 we cannot presume a direct causal relationship between such outcomes and SJL, which appears mostly as a variable that characterizes the study samples. Thus, we chose to exclude studies that did not explicitly assess illness Levandovski et al 2011 29 Roenneberg et al 2012 21 Johnsen et al 2013 22 Kantermann et al 2013 27 Schimitt et al 2013 35 Haraszti et al 2014 40 Kantermann et al 2014 25 Miller et al 2015 44 Rutters et al 2014 28 Borisenkov et al 2015 32 Parsons et al 2015 35 Tavernier et al 2015 42 Wong et al 2015 26 Choi et al 2016 45 Kolomeichuk et al 2016 38 Polugrudov et al 2016 24 Sheaves et al 2016 30 Silva et al 2016 46 Yong states or behavioral outcomes. Furthermore, it is very likely that sleep deficit correlates with SJL.…”
Section: Excluded Studies and Terminologymentioning
confidence: 99%
“…Choi et al 45 studied epileptic and healthy participants and found lower SJL in focal epilepsy patients than healthy controls and general epilepsy patients. Silva et al 46 assessed the quality of diet in undergraduate students, resulting in a negative association of SJL with servings per day of beans. Yet, the use of selfreported measures for both outcomes and SJL in these studies represents a high risk of detection bias and raises doubt about the reliability of such evidences.…”
mentioning
confidence: 99%